Bridging Gaps in Healthcare: Lessons learned from IMARET’s Primary Care Clinics Serving Refugees in Malaysia - Bin Yahaya, Ahmad Yusuf (International Journal of Human and Health Sciences (IJHHS), 2024)
Objectives: This paper presents an in-depth examination of a charitable primary care clinic dedicated to serving the healthcare needs of refugees in Malaysia. With the global refugee crisis on the rise, Malaysia has become home to a substantial refugee population facing numerous healthcare challenges due to their vulnerable status. In response to this pressing issue, our study focuses on a clinic that has been operating since 2021 as a beacon of hope, providing essential primary healthcare services to refugees from various countries. Methods: This paper explores the multifaceted dimensions of the clinic's operations, encompassing its inception, organizational structure, healthcare delivery model, and impact on the refugee population. The study employs quantitative data analysis derived from clinic records and demographic information. Results: This study highlights the clinic's critical role in addressing healthcare disparities among refugees in Malaysia. Our research reveals that the clinic not only offers vital medical care but also extends its services to encompass health education, psychosocial support, and cultural sensitivity training for its healthcare providers. In addition, this paper discusses the challenges faced by the clinic, including funding limitations, legal and administrative hurdles, and the evolving healthcare needs of the refugee population. We also delve into the innovative strategies employed by the clinic to navigate these challenges, such as partnerships with community leaders, collaborations with local healthcare institutions and international humanitarian organizations. Conclusion: Overall, this paper sheds light on the vital role of charitable primary care clinics in mitigating healthcare disparities among refugee populations. It underscores the need for continued support, both financial and logistical, to sustain and expand the reach of such clinics. By analyzing the experiences and lessons learned from this clinic, we aim to provide valuable insights for policymakers, humanitarian organizations, and healthcare providers, ultimately contributing to the enhancement of healthcare services for refugees in Malaysia and beyond. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S38